The Level of Environmental Concern in State Middle School Students in Yogyakarta City - Zudha Rahma Nur Azizah; Taat Wulandari (Proceeding International Conference on Religion, Science and Education, 2023)
This study aims to determine the level of environmental care of students in junior secondary adiwiyata schools in the city of Yogyakarta. The results showed that the level of environmental care of students in the Adiwiyata Junior High School in Yogyakarta City was in the category of very good tendency or 80,25%. This interest can be seen from various habits of caring for the environment, including (1) energy consumption with habits such as daily electricity use. (2) waste disposal, students are accustomed to sorting waste according to its type in the place provided. Waste that can be used by students as materials for making crafts. (3) keep the environment clean, students have carried out pickets according to schedule and participate in maintaining the surrounding public facilities. (4) adequate use of clean water and use of used water for other purposes. (5) use of carbon emissions to avoid the greenhouse effect and (6) use of fuels in moderation. If all schools implement the Adiwiyata program, the level of environmental awareness will increase.